A lung adenocarcinoma patient with co-mutations of MET and EGFR exon20 insertion responded to crizotinib - Yan Chen; Bo Jiang; Yuange He; Chu Zhang; Wenjie Zhou; Cheng Fang; Dejian Gu; Minxia Zhang; Mei Ji; Juntao Shi; Xin Yang (BMC, 2022)
Abstract Background Targeted therapy has revolutionized the treatment of patients with malignancies harboring mutations in driver genes and has brought a favorable survival benefit to the population with actionable oncogenic mutations. In recent years, the MET exon14 skipping mutation has been recognized as a potentially promising therapeutic target in non-small cell lung cancer (NSCLC). These changes are mutually exclusive with molecular drivers such as EGFR, KRAS, HER-2, BRAF, ALK and ROS1. The prevalence rate of coexisting MET exon 14 mutations and EGFR sensitive mutations (L858R, exon 19 deletions) in Chinese population was reported to be 0.2% (3/1590). However, the coexistence of MET exon 14 mutations with EGFR exon 20 insertion mutations has never been reported and the management of this subtype is not identified. Case presentation A 69-year-old male with a right lung adenocarcinoma (T4N2M0, IIIB) was confirmed to be positive for MET exon 14 skipping (c.3028_3028+1delGGinsTT, 44.4%), MET amplification (copy number 4.4), and EGFR exon 20 insertion (p. N771_H773dup, 22.1%) mutations. After the progression of one cycle of chemotherapy (Pemetrexed 0.8 g d1), the patient was subsequently accepted treatment with Crizotinib (250 mg twice a day) and achieved an important clinical remission for six months until the development of brain metastases. Then, he was submitted to a cycle of anti-programmed cell death-1 (PD-1) therapy after failure of Crizotinib and eventually acquired resistance despite of the high expression of programmed death ligand-1 (PD-L1) and tumor mutational burden (TMB) status. Conclusion This case report provides treatment strategies for epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs)-untreated lung adenocarcinoma patients simultaneously carrying MET alterations and EGFR exon 20 insertion mutations. In addition, the signatures of PD-L1 or TMB expression were not the candidate for predicting the efficacy of immunotherapy in this context.